Giving new life to old lungs: methods to produce and assess whole human paediatric bioengineered lungs. (12th January 2016) - Nichols, Joan E.; La Francesca, Saverio; Vega, Stephanie P.; Niles, Jean A.; Argueta, Lissenya B.; Riddle, Michael; Sakamoto, Jason; Vargas, Grace; Pal, Rahul; Woodson, Lee; Rhudy, Jessica; Lee, Dan; et al.
Abstract: We report, for the first time, the development of an organ culture system and protocols to support recellularization of whole acellular (AC) human paediatric lung scaffolds. The protocol for paediatric lung recellularization was developed using human transformed or immortalized cell lines and single human AC lung scaffolds. Using these surrogate cell populations, we identified cell number requirements, cell type and order of cell installations, flow rates and bioreactor management methods necessary for bioengineering whole lungs. Following the development of appropriate cell installation protocols, paediatric AC scaffolds were recellularized using primary lung alveolar epithelial cells (AECs), vascular cells and tracheal/bronchial cells isolated from discarded human adult lungs. Bioengineered paediatric lungs were shown to contain well‐developed vascular, respiratory epithelial and lung tissue, with evidence of alveolar–capillary junction formation. Types I and II AECs were found thoughout the paediatric lungs. Furthermore, surfactant protein‐C and ‐D and collagen I were produced in the bioengineered lungs, which resulted in normal lung compliance measurements. Although this is a first step in the process of developing tissues for transplantation, this study demonstrates the feasibility of producing bioengineered lungs for clinical use. Copyright © 2016 John Wiley & Sons, Ltd.